Structural Characterization and Hypolipidemic Activity of Highland Barley Polysaccharide-Polyphenol Complexes - Zibin GUO; Yang YANG; Bei FAN; Litao TONG; Yatao HUANG; Lili WANG; Ting ZHANG; Liya LIU; Peipei SUN; Jing SUN; Fengzhong WANG (Shipin gongye ke-ji)
This study aimed to isolate a polysaccharide-polyphenol complex (HVP) from highland barley grains and investigate its potential role in regulating lipid metabolism. The structural properties of HVP were characterized in preliminary studies, and its phenolic components before and after hydrolysis were qualitatively analyzed using a ultra-performance liquid chromatography-triple quadrupole tandem mass spectrometry (UPLC-TQMS-MS/MS) system. Furthermore, the lipid-lowering effects of HVP were assessed in a zebrafish hyperlipidemia model. The analysis revealed that HVP contained 494.4±13.0 mg/g of total sugars, 87.2±1.0 mg/g of total phenols, 47.6±1.0 mg/g of proteins, and 37.0±1.5 mg/g of uronic acids. The monosaccharide composition predominantly consisted of glucose and arabinose. Ferulic acid, apigenin, and hesperidin were identified in HVP before hydrolysis, while vanillin was identified as an additional component after hydrolysis. HVP markedly reduced oil red O staining in the caudal vasculature of zebrafish with hyperlipidemia (P<0.001). Additionally, HVP exhibited a dose-dependent effect on the reduction of triglyceride (TG) and total cholesterol (TC) levels in hyperlipidemic zebrafish, with the most pronounced effects observed at high doses (P<0.001). The structural characteristics and potential to regulate lipid metabolism of HVP provide new insights into its application in functional foods.